Strategies for finalizing conifers experimental tests to the production of improved reproductive materials - Ducci F.; Fusaro E.; Lucci S.; Ricciotti L. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The paper points out the ex situ conservation problems regarding genetic resources of the most important Mediterranean Conifers studied in Italy (Pinus halepensis, P. brutia, P. eldarica, P. pinaster, P. radiata; Cedrus atlantica, C. libani, Abies nebrodensis and other species). It prospects the possibility to use some experimental plantation, which reached fully fructification as a source of certified (known origin and controlled quality) propagation material. Council Directive 1999/105/EC on the marketing of forest reproductive material is drawn considering the possibility to certify conifer seeds within the different qualitative categories. Finally the paper presents the strategies to exploit appropriately experimental plantations in view of their correct management as seed orchards.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)